1996
DOI: 10.1084/jem.183.5.2293
|View full text |Cite
|
Sign up to set email alerts
|

Inducible nitric oxide synthase in pulmonary alveolar macrophages from patients with tuberculosis.

Abstract: SummaryThe high-output pathway of nitric oxide production helps protect mice from infection by several pathogens, including Mycobacterium tuberculosis. However, based on studies of cells cultured from blood, it is controversial whether human mononuclear phagocytes can express the corresponding inducible nitric oxide synthase (iNOS; NOS2). The present study examined alveolar macrophages fixed directly after bronchopulmonary lavage. An average of 65% of the macrophages from 11 of 11 patients with untreated, cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
311
2
4

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 449 publications
(332 citation statements)
references
References 53 publications
15
311
2
4
Order By: Relevance
“…are obligate intracellular parasites residing primarily in host macrophages. One of the most important antimicrobial effector molecules in murine macrophages is NO ⅐ (9, 10, 34), and a role for NO ⅐ in human macrophage microbicidal function has been documented in a few instances (29,35,36). NO ⅐ is produced from arginine by iNOS, the product of the NOS2 gene.…”
Section: Discussionmentioning
confidence: 99%
“…are obligate intracellular parasites residing primarily in host macrophages. One of the most important antimicrobial effector molecules in murine macrophages is NO ⅐ (9, 10, 34), and a role for NO ⅐ in human macrophage microbicidal function has been documented in a few instances (29,35,36). NO ⅐ is produced from arginine by iNOS, the product of the NOS2 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported that human macrophages do not produce as much NO in response to IFN-␥ as murine macrophages. 24,25 Therefore, transfection or introduction directly into the peritoneal cavity of the iNOS gene should generate higher levels of NO and result in a more direct and enhanced therapeutic modality. To make the treatment better, we are also actively investigating ways to enhance NO production and a synergistic tumor cytotoxicity of NO with TNF-␣ for the treatment of drug-resistant human ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…NO can be synthesized by different kinds of cells. Among these cells, macrophages play a pivotal role in the inflammatory infiltrate and, in patients with tubercolosis, iNOS is expressed in alveolar macrophages [6]. Inflammatory cells produce reactive oxygen species (ROS) that, reacting with NO, form tissue-damaging NO-derived inflammatory oxidants.…”
Section: Introductionmentioning
confidence: 99%